Signifikansi Pendekatan Sosiologis Terhadap Studi Keislaman - Vicky Izza El Rahma (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2019)
The sociology approach in Islamic studies has a significant contribution. The object of sociological studies in religious studies is that humans are devoted to the social aspects of their religions (religious communities). In the context of Islam, the dialectical relationship between the immaterial-sacred revelation of God and material-profane social processes is reflected in the decline of the verses of the MÄkiyyah and MadÄniyyah. By reading religion through a sociological approach, religion will not be reduced only as a set of normative-theological rules that produce black-and-white, right-wrong, halal-haram products, and so on. Religion will always be actual because it is not only applied as a song of revelation and is not ignorant of the real problems faced by society.